Q Fever in the Greek Island of Crete: Detection, Isolation, and Molecular Identification of Eight Strains of Coxiella burnetii from Clinical Samples - Spyridaki, Ioanna (American Society for Microbiology, 1998)
Over a period of 6 years (1989 to 1995), serum samples from 3,300 patients suspected to be infected by Coxiella burnetii were assayed for the presence of antibodies against antigen phase II of the microorganism by the indirect immunofluorescence antibody technique (IFAT). One hundred fifty-two cases were recorded, and blood samples from 17 patients were cultured for the isolation of the pathogen. By a centrifugation shell vial technique, eight strains were isolated from patients suffering from acute Q fever. The microorganism was detected in the cultures by IFAT, by Gimenez staining, and by the cytopathogenic effect on Vero and human embryonic lung (HEL) cells. PCR followed by restriction fragment length polymorphism analysis was used to confirm the diagnosis and identify the Coxiella burnetii strains within the cell cultures as well as to compare them with reference strains. In order to avoid time-consuming cultures, to achieve direct detection of Coxiella burnetii in clinical samples (blood, buffy coat, etc.), and to increase the specificity and sensitivity of the detection, nested PCR was performed. The first step of DNA extraction was performed with the QIAamp blood kit 250. For the second step of the PCR assays, the conditions of temperature and times of recycling were properly modified, and the microorganism was detected within 4 h. Our study demonstrates that Q fever is an endemic disease in Crete and that the diagnosis of Coxiella burnetii infection can be rapidly achieved by the detection of the microorganism in buffy coat samples by nested PCR. Although the presenting symptoms of the disease in this study differed from those in other studies, the Cretan strains do not differ genotypically from the reference strains (Nine Mile and Q212).